Iluminasi Mushaf Al-Qur’an Gunung Pring Sebagai Cerminan Seni dan Budaya Lokal - Muhamad Jamilan; Ahmad Saifudin; Titis Rosowulan (Syntax Idea)
This study aims to reveal the symbolic meaning and aesthetic value in the illumination of the Gunung Pring Qur'anic Mushaf as a reflection of local art and culture. Through an in-depth analysis of the motifs, colors, and composition of the illuminations, this research seeks to identify the influence of local art and culture on the development of Islamic art in the region. The research method used is descriptive qualitative based on the field of philological studies with semiotic and estetic approaches. The results show that the illumination of the Mushaf Al-Qur'an Gunung Pring is characterized by the use of local flora and fauna motifs as well as harmonious color combinations. These motifs contain symbolic meanings related to nature, life, and religious values of the local community. There are also influences of art styles from various regions, such as Persia and India, mixed with local elements. In conclusion, the illumination of the Mushaf Al-Qur'an of Gunung Pring is a representation of the combination of universal Islamic art with the peculiarities of local culture, so that it becomes a cultural heritage of high value and needs to be preserved.